The Impact of the Auckland Cellulitis Pathway on Length of Hospital Stay, Mortality Readmission Rate, and Antibiotic Stewardship. (26th February 2021) - Ritchie, Stephen R; Cutfield, Tim; Lee, Arier; Walter, Hannah; Gow, Robert; Gammie, Todd; Punnoose, Christy; Nagarkar, Suyog; Thomas, Mark G
Abstract: Background: The Dundee classification of cellulitis severity, previously shown to predict disease outcomes, provides an opportunity to improve the management of patients with cellulitis. Methods: We developed and implemented a pathway to guide the management of adults with cellulitis based on their Dundee severity class, and measured its effect on patient outcomes. We compared the outcomes in patients admitted to Auckland City Hospital (ACH) between July 2014 and July 2015 (the baseline cohort) with those in patients admitted between June 2017 and June 2018 (the intervention cohort). Results: The median length of stay was shorter in the intervention cohort (0.7 days, interquartile range (IQR) 0.1 to 3.0 days) than in the baseline cohort (1.8 days, IQR 0.1 to 4.4 days; P < .001). The 30-day mortality rate declined from 1.8% (19/1092) in the baseline cohort to 0.7% (10/1362; P = .02) in the intervention cohort. The 30-day cellulitis readmission rate increased from 6% in the baseline cohort to 11% ( P < .001) in the intervention cohort. Adherence to the ACH cellulitis antibiotic guideline improved from 38% to 48% ( P < .01) and was independently associated with reduced length of stay. Conclusions: The implementation of the Auckland cellulitis pathway, readily generalizable to other settings, improved the outcomes in patients with cellulitis, and resulted in an annual saving of approximately 1000 bed days. Abstract : The Auckland Cellulitis Pathway utilized the Dundee Cellulitis Classification and promoted oral antibiotic treatment for patients with mild disease. The pathway improved adherence to antibiotic guidelines, which resulted in reduced mortality and length of stay.